Das práticas marítimas à elaboração da imagem turísticade Fortaleza/Ceará - Aragão, Raimundo Freitas (2005)
The tourist image has a significant paper in the popularization of destinations and his/her elaboration has been used as important instrument of from Ceará political propaganda. For the propagation of those images the most different communication means are used: folders, brochures, videos, national and international magazines, among others. In that context, the present work treats of the use of supports institutional promotings as divulgers of the state political propaganda reaching diffusion so much national as international. In that way, the analysis bases on general and specific literature, in the reports of research of the General office of Tourism of Ceará (SETUR) and mainly in the materials institutional promotings produced by this organ. Consequently, the pres ent work verifies that the images that are transmitted of Ceará don't just detach the natural beauties of the State, but also the accomplishments (public works, infrastructure, etc.), the successes and the local rulers' conquests, starting from the "governo das mudanças" (government of the changes), being for this transformed in political propaganda for the same ones.